The Effect of Variation in Solvent Concentration on Caffeine Content in Green Arabica Coffee Bean Extract (Coffea arabica) using UV-Vis Spectrophotometry - Zulfaidah, Nanda Tsalasani; Kurniawati , Endah; Putri, Gita Herdittya; Widiani, Fitria (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Coffee is one type of beverage that is widely favoured by the community, Arabica coffee plants are a variant that grows a lot in Indonesia. Coffee beans contain various chemical compounds, one of which is caffeine. This study aims to determine the caffeine content with different solvent concentrations. Green Arabica coffee beans (Coffea arabica) were extracted using the maceration method. Ethanol extract 70% and ethanol extract 96% of green Arabica coffee beans were then fractionated in liquid-liquid extraction of chloroform and water phases. Then the analysis and determination of caffeine content were carried out with a UV-Vis Spectrophotometer. Qualitative tests were carried out using the Parry reagent color test showing positive results with a change in color to green. The results of the study in the form of a % caffeine content value to the weight of the extract sample, showed that in the 70% ethanol extract of green Arabica coffee beans contained a caffeine content of 10.115 ± 0.06% and the 96% ethanol extract of green Arabica coffee beans was 12.760 ± 0.580%. The results of the analysis showed that the amount of caffeine content had a significant difference with a p-value <0.05. So it can be concluded that the optimum solvent for extracting caffeine from green Arabica coffee bean extract is 96% solvent.